2006
DOI: 10.1007/s10802-006-9035-x
|View full text |Cite
|
Sign up to set email alerts
|

Do Provocateurs’ Emotion Displays Influence Children’s Social Goals and Problem Solving?

Abstract: The social goals and social problem-solving of children who varied in social adjustment were examined in the context of hypothetical ambiguous provocation situations in which provocateurs' emotion displays were systematically manipulated. Children rated the importance of six different social goals and explained how they would solve the problems. Social adjustment was measured with rating and nomination sociometric procedures. Rejected-aggressive, rejected-nonaggressive, average-nonaggressive, and popular-nonag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
30
1
5

Year Published

2009
2009
2019
2019

Publication Types

Select...
2
2
2

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(42 citation statements)
references
References 48 publications
(77 reference statements)
6
30
1
5
Order By: Relevance
“…However, a study of naturally occurring conflicts showed that 7-to 11-year-old's self reports of anger during conflict were associated with less friendly goals, and anger intensity was negatively correlated with constructive behavior during the course of the conflict (Murphy and Eisenberg 2002). These results are consistent with findings on SIP in the context of hypothetical video-taped ambiguous provocations in which the emotional displays (happy, angry, sad) of provocateurs were systematically manipulated, and the SIP of rejected-aggressive, rejected-nonaggressive, averagenonaggressive, and popular-nonaggressive first, third and fifth graders was compared (Lemerise et al 2006). When provocateurs were happy, there were few differences in importance ratings of social goals or friendliness of social problem-solving responses.…”
Section: Goal Clarificationsupporting
confidence: 80%
See 4 more Smart Citations
“…However, a study of naturally occurring conflicts showed that 7-to 11-year-old's self reports of anger during conflict were associated with less friendly goals, and anger intensity was negatively correlated with constructive behavior during the course of the conflict (Murphy and Eisenberg 2002). These results are consistent with findings on SIP in the context of hypothetical video-taped ambiguous provocations in which the emotional displays (happy, angry, sad) of provocateurs were systematically manipulated, and the SIP of rejected-aggressive, rejected-nonaggressive, averagenonaggressive, and popular-nonaggressive first, third and fifth graders was compared (Lemerise et al 2006). When provocateurs were happy, there were few differences in importance ratings of social goals or friendliness of social problem-solving responses.…”
Section: Goal Clarificationsupporting
confidence: 80%
“…In adolescents, endorsement of revenge and dominance goals is associated with a variety of problems ranging from depression, aggression, and low sociability to crimes against persons and substance abuse (Lochman et al 1993). Moreover, rejected-aggressive children not only favor more self-focussed and instrumental goals, they also show less evidence of being able to coordinate and integrate multiple social goals in both conflict and cooperative situations (Lemerise et al 2006;Rabiner and Gordon 1992).…”
Section: Goal Clarificationmentioning
confidence: 99%
See 3 more Smart Citations